Fine-grained volcanic-hydrothermal sedimentary rocks in Permian Lucaogou Formation, Santanghu Basin, NW China: Implications on hydrocarbon source rocks and accumulation in lacustrine rift basins. (April 2020) - Jiao, Xin; Liu, Yi-qun; Yang, Wan; Zhou, Ding-wu; Bai, Bin; Zhang, Tian-shu; Zhao, Min-ru; Li, Zhe-xuan; Meng, Zi-yuan; Yang, Yi-yao; Li, Zhi-xin
Abstract: Subaqueous volcanic-hydrothermal field is a complex hybrid geological system, where sediments originated from volcanic, hydrothermal, lacustrine, terrestrial, and biotic sources are mixed. Recent petrological studies on such sediments have indicated a potential relationship between volcanic-hydrothermal activities and oil generation and accumulation. Here, we explore the mechanisms of sedimentation and oil accumulation in well-laminated organic-rich fine-grained sedimentary rocks in Permian Lucaogou Formation deposited in the lacustrine Santanghu rift basin, NW China. We conducted petrographic, carbon and oxygen isotopic, and organic geochemical analyses of fifty-four core samples from three wells (forty-eight samples from Well W1, two from W2, four from W3) designed for tight oil exploration. Four main observations and interpretations are: 1) The fine-grained sediments are a mixture of volcanic-hydrothermal detrital feldspar grains, authigenic quartz crystals, and primary lacustrine dolomite, forming interbedded tuffaceous shale and dolostone; 2) authigenic quartz crystals were precipitated from acidic hydrothermal fluids, whereas fine-grained angular alkaline feldspars were derived from subaqueous volcanic eruption; 3) the TOC content and oil generation potential increase with increased mixing of feldspars and carbonate minerals. Hence, the dolomite-bearing tuffaceous shale and tuffaceous dolostone are the best source rocks; and 4) the fine-grained sedimentary rocks are interpreted as a subaqueous volcanic-hydrothermal deposit that controls the source potential. The sedimentary processes of an ancient sediment-hosted geothermal system and its implications on hydrocarbon source rocks and accumulation were first identified. Algal bloom induced by subaqueous eruptions is the main cause for episodic deposition of organic matter and extreme heterogeneity in both lithofacies and source-rock distribution. The results suggest that cone-shaped buildups on seismic sections, which were formed by volcanic-hydrothermal deposits and contain highly-mixed feldspar and carbonate sediments, are the best hydrocarbon reservoirs, and demonstrate a strong relationship between volcanic-hydrothermal activities and hydrocarbon accumulation in an extensional tectonic setting. Highlights: Oil-bearing shales contain abundant volcanic-hydrothermal sediments. Subaqueous volcanic-hydrothermal and lake sediments mixed in a rift basin. Most quartz was precipitated from acidic-hydrothermal fluid before compaction. Algae are the main organic matter and grew by volcanic-hydrothermal nutrients. Lithofacies of mixed minerals near cone-shaped body on seismic are oil targets.